How can unions use Artificial Intelligence to build power? The use of AI chatbots for labour organising in the US and Australia. (12th December 2020) - Flanagan, Frances; Walker, Michael
Abstract : Artificial intelligence increasingly forms an essential context for the distribution of power within workplaces. Using the case study of an AI‐enabled chatbot initially created by IBM and subsequently developed by an alt‐labour network in the United States and a traditional union in Australia, this article outlines several distinctive ways in which the chatbot increased union resources and capabilities. Once reconfigured to reflect an 'organising', rather than 'servicing' ethos, the chatbot became an infrastructural resource that enabled otherwise marginal workers to receive basic information in a manner that reinforced union narratives of power and worker solidarity, and workplaces to be mapped more efficiently. The chatbot did not act as a labour saving tool, but stimulated wide‐ranging learning by bringing implicit tensions between 'servicing' and 'organising' conceptions of knowledge, power and expertise to the surface. Chatbots thus offer distinctive potential affordances to unions in enhancing their resources and capabilities as 'orchestrators' of worker power.